Caregivers of children with Down syndrome: reflections on the context of life - Oliveira, Joseilse Rosângela de (2022)
The objective was to understand the life context of caregivers of children with Down Syndrome. This is a descriptive, exploratory study with a qualitative approach. The study had as participants the caregivers of children with Down Syndrome who lived in a municipality in the interior of Ceará. Data collection was carried out using a semi-structured interview script. Data analysis was performed using the content analysis technique proposed by Minayo. The research complied with all the ethical precepts of Resolution 466/2012, which deals with studies carried out with human beings. Eleven caregivers of children with DS from zero to nine years old participated. It was possible to identify the caregivers' knowledge about the syndrome and capture several components belonging to the DS diagnosis that can interfere in the family's adaptation process, as well as situations of vulnerability that arise in front of it. Participants report negative experiences at the beginning of the discovery, however, when becoming familiar with DS, they express appreciation for the situation of having a child with DS. In relation to coping, the strength found in religion and family stands out. The research contributed to identify the weaknesses found in the diagnosis and the care dedicated to the child with DS by their caregiver, to expand the professionals' knowledge about the adaptation process in which the family with DS suffers.